WASP: the World Archives of Species Perception. (28th February 2023) - Nguyen, Tuan; Malina, Robert; Mokas, Ilias; Papakonstantinou, Antonis; Polyzos, Orestes; Vanhove, Maarten P M
Abstract: While human perception can play a role in influencing public support for species conservation, the mechanisms underlying human perception remain poorly understood. Some previous studies on perception have focused on a few specific taxa, which makes the understanding of the public perception of species at large a resource- and time-intensive task. Here, we introduce the World Archives of Species Perception project that consists of an animal survey and a plant survey to construct the first systematic database to study the human perception of the floral and faunal diversity at a global scale. We provide a description of our survey method, species selection, survey implementation and a discussion of the potential uses of our databases in multidisciplinary research. In the animal survey, we cover 1980 International Union for Conservation of Nature (IUCN)–evaluated species, representing 25 classes, 192 orders, 1037 families and 1705 genera. In the plant survey, we cover 2000 IUCN-evaluated species, representing 13 classes, 93 orders, 386 families and 1968 genera. Data from the survey will be collected and made available 24 months after the publication of the article. Database URL http://wasp-project.net/